2020
DOI: 10.3390/biom10050795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chenopodin Isoforms from Quinoa Seeds and Assessment of Their Potential Anti-Inflammatory Activity in Caco-2 Cells

Abstract: Several food-derived molecules, including proteins and peptides, can show bioactivities toward the promotion of well-being and disease prevention in humans. There is still a lack of information about the potential effects on immune and inflammatory responses in mammalian cells following the ingestion of seed storage proteins. This study, for the first time, describes the potential immunomodulation capacity of chenopodin, the major protein component of quinoa seeds. After characterizing the molecular features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Quinoa albumin was the most active fraction, showing a 74% inflammation reduction. The immune-modulating effects of quinoa LC and HC globulin fractions are similar to those previously described [ 45 ] and are slightly higher than those of amaranth and buckwheat globulins. In the present study, we demonstrated that amaranth, buckwheat, and quinoa seed proteins potentially modulate an inflammation response by decreasing NF-κB activation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Quinoa albumin was the most active fraction, showing a 74% inflammation reduction. The immune-modulating effects of quinoa LC and HC globulin fractions are similar to those previously described [ 45 ] and are slightly higher than those of amaranth and buckwheat globulins. In the present study, we demonstrated that amaranth, buckwheat, and quinoa seed proteins potentially modulate an inflammation response by decreasing NF-κB activation.…”
Section: Resultssupporting
confidence: 85%
“…Notably, the SDS-PAGE pattern was very similar to that of the salt-soluble fraction obtained following isoelectric precipitation of chenopodins, as shown by Brinegar et al [ 44 ], and very different from the two retained LC and HC fractions. These two fractions include isoforms of the 11–13S globulin chenopodin, the main quinoa SSPs [ 45 ]. The bands with molecular weights (MWs) of 35–37 and 22–25 kDa correspond to the α and β chains of chenopodin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Quinoa ( C. quinoa Willd.) seeds store about 12–15% of proteins with high biological value ( Capraro et al, 2020 ). Our current studies show that soil salinity affected the amino acid content in quinoa seeds to a much lesser extent than the FA content.…”
Section: Discussionmentioning
confidence: 99%
“…Caco-2 cells were cultivated as previously described [ 46 ] and were seeded in 12-multiwell plates. The experiments were initiated on day 3 after cells reached confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of the different molecules on inflammation were expressed as fold change in target genes expression relatively to the untreated control sample. qPCR was carried out as described in Capraro et al [ 46 ]. Primers for amplification of IL-8 expressed gene were: 5-ATGACTTCCAAGCTGGCCGTGGCT-3 and 5-TCTCAGCCCTCTTCAAAAACTTCTC-3.…”
Section: Methodsmentioning
confidence: 99%